„Chcę rozmawiać”. Autopsychoterapeutyczne funkcje narracji Justyny Bargielskiej i Anny Starobiniec o utracie perinatalnej - Adelgejm, Irina (Postscriptum Polonistyczne, 2020)
The article discusses a unique experience of death such as a perinatal loss described in Obsoletki by Justyna Bargielska and Spójrz na niego by Anna Starobiniec. The author of the article analyses the ways in which narration aims at assimilating the traumatic experience (in Bargielska’s writing: ‘cataloguing’ the pain of other mothers, ‘a split screen’, adapting external observer’s point of view, dividing the trauma into separate elements, lack of logic; in Starobiniec’s writing: externalization of the loss by the experience of mourning, ‘recreating’ lost relations; in both authors’ creativity: connecting life and death, placing loss in the story of life, conventional endings).